Influence of drying methods on the texture profile characteristics of the button mushroom, Agaricus bisporus - Arumuganathan, T; Manikantan, M R; Indurani, C; Khare, Vinay; Tiwari, R P; Rai, R D (Mushroom Research, 2015)
Please see the full text